Information Website on JASDAM II Sriwijaya - Sari, Dhea Nadita; Amalia, Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Information Website on Jasdam II Sriwijaya is a form of rapid information technology created with the aim of making Jasdam II Sriwijaya more exposed and making it easier for the public to obtain or find out any information about Jasdam II Sriwijaya and aims to promote Jasdam II Sriwijaya. The system development method used is arranged in four stages, namely 1) planning, 2) Design 3) Coding, 4) Testing. This website-based application was created within four months, from 18 September to 18 December. This website-based application produces benefits because with the information website at Jasdam II Sriwijaya, many people come to Jasdam II Sriwijaya to exercise using the facilities provided at Jasdam II Sriwijaya.